Left ventricular ejection fraction decrease related to BRAF and/or MEK inhibitors in metastatic melanoma patients: A retrospective analysis. (14th February 2020) - Berger, Mathilde; Amini‐Adlé, Mona; Maucort‐Boulch, Delphine; Robinson, Philip; Thomas, Luc; Dalle, Stéphane; Courand, Pierre‐Yves
Abstract: BRAF and MEKis have revolutionized the management of BRAF V600 ‐mutated melanoma patients. Left ventricular ejection fraction decrease (LVEF‐D) related to these treatments has not been thoroughly evaluated to date. The main objective of this study was to describe characteristics of LVEF‐D in melanoma patients treated with BRAF and/or MEKis. Metastatic melanoma patients treated with BRAF and/or MEKis between March 1, 2012 and May 18, 2018 were included retrospectively (Lyon Sud University Hospital, Hospices Civils de Lyon). LVEF‐D was defined as a reduction in LVEF ≥10% from baseline to a value <55%; normalization was defined as a value ≥55%. Among the 88 patients included, 12 (13.6%) experienced a LVEF‐D, including 10 grade 2 and 2 grade 3. The median onset of which was 11 months (IQR [3‐21]). No patient previously treated with beta‐blockers (n = 12) experienced a LVEF‐D. Analysis of laboratory parameters, electrocardiogram, and transthoracic echocardiography during the follow‐up did not find any predictive marker of LVEF‐D. All patients who benefited from a specific treatment of LVEF‐D had a normalization of LVEF at the end of follow‐up. LVEF recovery was significantly better for patients treated with angiotensin converting enzyme inhibitors and beta‐blockers than those who did not ( P  = .019). Ophthalmological adverse events were significantly more frequent in patients who experienced a LVEF‐D ( P  = .006) and the latter did not influence overall‐survival ( P  = .117) or progression‐free‐survival ( P  = .297). LVEF‐D is a common and easily manageable adverse event due to BRAF and MEKis. Its association with ocular toxicity suggests a close ophthalmological monitoring when LVEF‐D occurs. Abstract : Left ventricular ejection fraction decreased was observed in 13.6% of patients treated with BRAF and MEK inhibitors. All patients treated with beta‐blockers and/or angiotensin converting enzyme inhibitors had a normalization of left ventricular ejection fraction. Half of patients with left ventricular ejection fraction decreased had also ophthalmologic adverse event.